2007
DOI: 10.1038/sj.bmt.1705820
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of secondary failure of platelet recovery after autologous and syngeneic peripheral blood stem cell transplantation in acute promyelocytic leukemia

Abstract: Secondary failure of platelet recovery (SFPR), which is a delayed decline in platelet count after primary recovery following myeloablative hematopoietic SCT, is a significant problem in allogeneic SCT. However, its clinical characteristics have not been well described in autologous SCT for acute myeloid leukemia. We reviewed 11 consecutive patients who had received autologous or syngeneic SCT for acute promyelocytic leukemia. Seven of 11 patients (64%) had SFPR, which is defined as a decline in the platelet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Patients who attained a target CD341 cell dose of 2.0 3 10 6 /kg or higher were allocated to undergo autologous HCT unless PML-RARa transcripts were detected in PBSCs. The conditioning regimen consisted of busulfan (1 mg/kg orally every 6 hours on days 26 to 24) and melphalan (70 mg/m 2 intravenously on days 23 to 22), 13 whereas unpurged autologous PBSCs were infused on day 0. The study flow is shown in Figure 1.…”
Section: Treatmentsmentioning
confidence: 99%
“…Patients who attained a target CD341 cell dose of 2.0 3 10 6 /kg or higher were allocated to undergo autologous HCT unless PML-RARa transcripts were detected in PBSCs. The conditioning regimen consisted of busulfan (1 mg/kg orally every 6 hours on days 26 to 24) and melphalan (70 mg/m 2 intravenously on days 23 to 22), 13 whereas unpurged autologous PBSCs were infused on day 0. The study flow is shown in Figure 1.…”
Section: Treatmentsmentioning
confidence: 99%
“…The patient described in this report also exhibited secondary failure of platelet recovery, which occurs in 8% of patients undergoing autologous transplantation (peaking at 64% in acute promyelocytic leukemia patients due to busulfan-containing regimens [Narimatsu et al, 2007]), with a median time of onset after transplantation at day þ44 (range, days 24-89), and concomitant neutropenia is seen in 19% of these patients [Bruno et al, 2001]. HCMV infection occurring after engraftment, and marrow rather than peripheral blood as the source of hematopoietic stem cells are the only significant risk factors [Nash et al, 1996].…”
Section: Discussionmentioning
confidence: 87%
“…26,28 Although the phenomenon has been well described among allogeneic transplant patients, very few reports are available in the literature for autologous transplant patients, more so in AML patients. 37,38 The few studies that have reported their observations on the effect of secondary thrombocytopenia on patients' survival and outcome in AML post-autologous transplantation had small numbers of AML patients in their study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study by Bruno et al 27 on various malignancies reported an incidence of 19% among their autologous transplant patients. Narimatsu et al 28 from Japan reported a high incidence of secondary thrombocytopenia (64%) in their study of patients with acute promyelocytic leukemia who had autologous and syngeneic SCT. The higher incidence of secondary thrombocytopenia observed in their study might be due to the smaller sample size (7 out of 11 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation